The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40537-020-00390-x
|View full text |Cite
|
Sign up to set email alerts
|

Resampling imbalanced data for network intrusion detection datasets

Abstract: Machine learning plays an increasingly significant role in the building of Network Intrusion Detection Systems. However, machine learning models trained with imbalanced cybersecurity data cannot recognize minority data, hence attacks, effectively. One way to address this issue is to use resampling, which adjusts the ratio between the different classes, making the data more balanced. This research looks at resampling’s influence on the performance of Artificial Neural Network multi-class classifiers. The resamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 25 publications
0
83
0
2
Order By: Relevance
“…While the model proposed by Koroniotis et al (2017) achieved 93.23% accuracy using DT classifier. In addition, none of the studies listed in Table 1 have resolved the class imbalance problem of the UNSW-NB15 dataset as there are many studies ( Al-Daweri et al, 2020 ; Ahmad et al, 2021 ; Bagui & Li, 2021 ; Dlamini & Fahim, 2021 ) that have highlighted this issue. We addressed the class imbalance problem by applying SMOTE that improved the performance of the classifiers and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…While the model proposed by Koroniotis et al (2017) achieved 93.23% accuracy using DT classifier. In addition, none of the studies listed in Table 1 have resolved the class imbalance problem of the UNSW-NB15 dataset as there are many studies ( Al-Daweri et al, 2020 ; Ahmad et al, 2021 ; Bagui & Li, 2021 ; Dlamini & Fahim, 2021 ) that have highlighted this issue. We addressed the class imbalance problem by applying SMOTE that improved the performance of the classifiers and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…Pahl et al [15] describe in their paper that even though there is some related work found in IoT, still it is attracting the attention of researchers for its popularity in today's livelihood and designed an anomaly-based detector and firewall for IoT system using K-Means and BIRCH clustering with a predictive accuracy of 96.3%. Brun et al [16] Bagui and Li [26] presented the usefulness of random oversampling and random under-sampling with SMOTE to deal with highly imbalanced and less imbalanced intrusion detection datasets to improve the classification accuracy of the classifier. They evaluated the model by using artificial neural network (ANN) for attack detection using macro precision; macro recall, and macro F1 score for several sampling techniques and found that SMOTE-Random under-sampling with ANN classifier outperforms all others with 83.61% macro precision; 87.14% macro recall; 82.75% macro F1-score with 342 seconds training time.…”
Section: Related Researchmentioning
confidence: 99%
“…Liaqat et al [41] used the up-sampling method to increase the number of benign samples in the training data set. In [42][43][44][45], Synthetic Minority Oversampling Technique (SMOTE) method was used to generate additional samples for the minority classes. Mulyanto et al [46] performed feature selection to reduce dimensionality while focal loss function was used to address class imbalance problem.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Recent studies recommended SMOTE as an efficient over-sampling method [42][43][44][45]47,51]. Therefore, SMOTE algorithm was proposed to deal with the high class imbalance problem in the training set in an 11-class classification scenario.…”
Section: Synthetic Minority Oversampling Techniquementioning
confidence: 99%